Clarifying the identity of Geastrum campestre var. famatinum (Geastrales, Basidiomycota) - Zamora, Juan Carlos; Dios, Maria Martha; Moreno, Gabriel (Phytotaxa, 2017)
The identity of the holotype specimen of G. campestre var. famatinum is investigated through both morphological and molecular approaches. Morphological data and molecular data of ITS, 28S, rpb1 and atp6 DNA regions confirm that G. campestre var. famatinum is a different species to G. campestre var. campestre, and that it should belong to G. sect. Hariotia instead of G. sect. Campestria. However, the analyses performed also show that the type specimen of G. campestre var. famatinum is better included within the intraspecific variation of a previously described species, G. parvisporum, so both names are considered as heterotypic synonyms.